Variation on growth and yield traits among selected Phaseolus vulgaris landraces in KwaZulu-Natal, South Africa - VALENCIA VUYISILE NDLANGAMANDLA; NONTUTHUKO ROSEMARY NTULI (Society for Indonesian Biodiversity, 2019)
Abstract. Ndlangamandla VV, Ntuli NR. 2019. Variation on growth and yield traits among selected Phaseolus vulgaris landraces in KwaZulu-Natal, South Africa. Biodiversitas 20: 1597-1605. Phaseolus vulgaris L. (common bean) of American origin is grown worldwide for edible leaves, immature pods and dry seeds. This is the first comprehensive study conducted on variation among P. vulgaris landraces in South Africa. This study aimed to characterize variability in morpho-agronomic traits of P. vulgaris landraces. Twenty landraces were planted in a randomized complete block design with three replications. Variations in germination percentage as well as in stem, leaf, pod and seed traits were determined. Significant variations were recorded in all vegetative and reproductive traits except germination percentage and seed thickness. Vegetative traits correlated positively with each other, whereas reproductive traits correlated positively with both traits. Positive association of almost all traits with first and second components in a principal component analysis and biplot indicated them as potential discriminatory traits for landraces. The biplot and dendrogram associated landraces mainly according to their seed colour as well as growth and yield traits. This study revealed the potential vegetative and reproductive traits that can be used to select vigorously growing and high-yielding P. vulgaris landraces for future large-scale farming and breeding in South Africa. These traits could potentially result in desired plants with big stems, many branches, and numerous and broad leaves with high chlorophyll content, which will yield many, long and wide pods as well as many and heavy seeds. The taller landraces (D-50M50LB-Cl, D-50P50C-Cl, E-100YG-Cl, E-25YG-Cu, E-50M50LB-Cu, E-50B50C-Cl and E-50DB50C-Cl) from KwaZulu-Natal show good potential for future large-scale farming and breeding for vigorous growth as well as high pod and seed yield.